2017
DOI: 10.1016/j.socscimed.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Parents' transitions into and out of work-family conflict and children's mental health: Longitudinal influence via family functioning

Abstract: The demands arising from the combination of work and family roles can generate conflicts (work-family conflicts), which have become recognized as major social determinants of mothers' and fathers' mental health. This raises the question of the potential effects on children. The current study of 2496 Australian families (7652 observations from children aged 4-5 up to 12-13 years) asks whether changes in children's mental health corresponds with changes in mothers' and fathers' work-family conflicts. Using longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 50 publications
(58 reference statements)
5
92
0
Order By: Relevance
“…And, while parents with optimal mental health have capacity to provide warm, nurturing and stimulating environments for their children, parental stress and mental health difficulties are related with poorer quality parent-child interactions, with less warmth, more irritability and less consistency (Conger et al, 2002). Recent longitudinal research of work-family conflict and children's mental health (Dinh et al, 2017) showed that when parents move into work-family conflict and when it becomes chronic, children's wellbeing is adversely affected both directly and indirectly via increases in poor parent mental health, parenting irritability and marital dissatisfaction.…”
Section: The Connection Between Parenting Styles and Conflict Of Rolesmentioning
confidence: 99%
“…And, while parents with optimal mental health have capacity to provide warm, nurturing and stimulating environments for their children, parental stress and mental health difficulties are related with poorer quality parent-child interactions, with less warmth, more irritability and less consistency (Conger et al, 2002). Recent longitudinal research of work-family conflict and children's mental health (Dinh et al, 2017) showed that when parents move into work-family conflict and when it becomes chronic, children's wellbeing is adversely affected both directly and indirectly via increases in poor parent mental health, parenting irritability and marital dissatisfaction.…”
Section: The Connection Between Parenting Styles and Conflict Of Rolesmentioning
confidence: 99%
“…With a few exceptions (e.g., Dinh et al, 2017;Ferreira et al, 2018), the existing research on the associations between the work-family interface and child behavioral problems used cross-sectional study designs, limiting our understanding in two important ways. Firstly, associations between the work-family interface and child behavioral problems have been investigated separately in childhood or adolescence, but not together, which limits our understanding of developmental effects (for an exception, see Vahedi, Krug, Fuller-Tyszkiewicz, & Westrupp, 2018).…”
Section: P O S T -P R I N Tmentioning
confidence: 99%
“…In terms of empirical support, emerging evidence indicates that work-family experiences influence partners' relationship and the level of inter-parental conflict (Cooklin et al, 2015;Dinh et al, 2017); and a large body of research demonstrates the negative impacts of inter-parental conflict on child mental health (e.g., Cummings, George, McCoy, & Davies, 2012). Inter-parental conflict is also one of the family-based environmental factors that may be involved with the development of emotional insecurity and disordered eating in adolescents (George, Fairchild, Cummings, & Davies, 2014).…”
Section: P O S T -P R I N Tmentioning
confidence: 99%
See 2 more Smart Citations